Palesoeismological investigations of the Eastern part of the Khlong Marui fault zone in Surat Thani province, Southern Thailand. - Prakrit Noppradit (Prince of Songkla University, 2014)
Thesis (M.Sc., Geophysics)--Prince of Songkla University, 2013